Concentration of dentin sialoprotein at the initial stage of orthodontic treatment using self-ligating and conventional preadjusted brackets: A pilot study - Muhammad Sulaiman Kusumah Adiwirya; Retno Widayati; Nurtami Soedarsono; Haru Setyo Anggani (Journal of Orthodontic Science, 2022)
OBJECTIVES: This study evaluated differences in concentration of dentin sialoprotein (DSP) in gingival crevicular fluid (GCF) relating to orthodontically induced inflammatory root resorption (OIIRR) at the initial stage of orthodontic treatment using self-ligating and conventional preadjusted brackets. MATERIALS AND METHODS: Eighteen patients were assigned to three groups of equal size. Two experimental groups received non-extraction orthodontic treatment using passive self-ligating or conventional preadjusted bracket. The control group included patients without orthodontic treatment. GCF was collected from five proximal sites of maxillary anterior teeth at subsequent intervals: immediately prior to orthodontic treatment (T0), and at three and 12 weeks after initiation of treatment (T1 and T2). DSP concentration was evaluated by enzyme-linked immunoabsorbent assay and the differences in DSP levels were analyzed between and within groups. RESULTS: There were no significant differences in DSP levels within both experimental groups and the control group during T0-T1-T2 (P ≥ 0.05). A significant difference of DSP concentration was found between the conventional preadjusted bracket and the control group at T2 (P = 0.038). However, it was thought to be clinically insignificant. CONCLUSION: The study showed no significant difference in DSP concentration at the initial stage of orthodontic treatment with either self-ligating or conventional preadjusted bracket.